Knowledge, attitudes and practices of adolescent school girls regarding prevention of iron deficiency anaemia - Upadrasta, Venkata Prasad; Ponna, Satyendra Nath; Bathina, Hemalatha; S., Bharathi; Kapu, Ashok Kumar Reddy; Sadasivuni, Renuka; Mitaigiri, Chandini (International Journal Of Community Medicine And Public Health, 2019)
Background: Anaemia is very prevalent in adolescent girls, especially in developing countries like India. Treatment of anaemia based on the cause during adolescence decreases morbidity and mortality during early pregnancy. Despite weekly iron and folic acid supplementation programmes, the prevalence of anaemia among women and adolescent girls is still high. The objective of the study was to assess the proportion of anaemia and its determinants among adolescent school girls. Methods: An observational study was conducted in adolescent school girls of Chandragiri from January to March, 2018. Demographic data, knowledge and practices of personal hygiene were collected. Nutritional status was assessed by collecting anthropometric, body composition measurements, dietary habits and haemoglobin was estimated. Results: Of the 111 girls studied, 55.9% were found to be anaemic. Knowledge and practices of personal hygiene was lower in anaemic girls compared to non-anaemic girls. The extent of deficit of iron rich food consumption was low in both anaemic and non-anaemic girls. Conclusions: Prevalence of mild anaemia was high and iron rich foods intake was low in our study subjects. Assessment of burden of anaemia among adolescent girls is essential to address gaps in implementation of public health programs and effective intervention programs can be designed to reduce the burden of anaemia.